Analysis and modeling of database storage optimization power consumption usage for green data centers - Wan Noor Hamiza, Wan Ali (2014)
Data centers comprised of the building block of Internet Technology (IT) business organizations holding the capabilities of centralized repository for storage, management, networking and dissemination of data. The data centers consumed a lot of energy in order to ensure all the processes in data centers running completely every second which this situation can be lead to increase carbon footprint and give negative impact to the world (global warming). One way to reduce the energy consumption is by optimizing space storage in data centers. Thus, the proxy-based approach is used to optimize the space storage in CMR database in order to establish green data centers. This technique requires proxy candidate in order to drop some attribute for decrease the space storage. The proxies can be discovered by using a developed algorithm of functional dependencies (FDs) called as TANE algorithm. By using TANE algorithm, the proxy candidate and droppable attribute for table in CMR database can be discovered before the space saving can be calculate by given formula. The power saving can be calculated after the amount of space saving is known. The correlation between amount of space saving and amount of power saving was visualized in form of graph in the green data center correlation tool. The project concludes the result from the experiment achieved all the objectives and answered all the research questions.